Analisis Kesulitan dan Strategi dalam Pengerjaan TOEFL Listening - Dewi Puruhita Suci; Eliyani; Shofia Ash’Saudah; Nor Asifa; Khairil Anwar; Muhammad Nabil Muzakki; Kamilatunisa Isobir (LANCAH: Jurnal Inovasi dan Tren, 2025)
This study aims to analyze the difficulties and strategies used by participants in facing the Listening Section of the TOEFL test. The study used a mixed-methods approach, employing a survey and qualitative analysis of twelve respondents who had taken the TOEFL. Data were collected through questionnaires and analyzed descriptively to illustrate patterns of difficulty and thematically to explain the strategies used by participants.The results showed that the most challenging section was Part C (long conversation), where participants experienced difficulties understanding the academic context and the speaker's pace. The main obstacles included linguistic, psychological, and technical factors. This finding aligns with theories in several referenced TOEFL modules, as well as research by Silviyanti, Rahmadhani, & Samad (2020), which showed a tendency toward the use of form-centric strategies. An article by TST Prep (2024) reinforces these findings by emphasizing the importance of active and contextual listening practice. Therefore, this study concludes that improving TOEFL listening skills requires continuous practice, the application of meaning-based strategies, and the consistent practice of listening to authentic materials.